التجربة السنغافورية في تجاوز الفقر وتحقيق التنمية: رؤية تحليلية سوسيو اقتصادية لأسرار النجاح - حمزة، عبدالحفيظ Hamzah, Abdulhafiz; دنمبري، لطفي Denberi, Lutfi (جامعة محمد خيضر بسكرة - كلية العلوم الإنسانية والاجتماعية, 2019)
يروم هذا البحث إلى استعراض تجربة من أهم التجارب الدولية الرائدة في مكافحة الفقر، ويتعلق الأمر هنا بالتجربة السنغافورية؛ فما وصلت إليه هذه الدولة من نماء وتطور ورخاء جلب أنظار العالم، واسترعى اهتمام المفكرين، واستدعى الكثير من الباحثين والدارسين لطرق أبواب البحث والدراسة في موضوع هذه التجربة الرائدة. إن الفقر الذي كان الشعب السنغافوري يعيشه ويعاني من ويلاته تسببت فيه عوامل عدة؛ منها التاريخية كتعرضه للحروب والاحتلال من قبل البريطانيين واليابانيين، والانفصال عن الاتحاد الماليزي عام 1965، والنزاعات العرقية، ومنها الجغرافية والمتمثلة في ضيق المساحة الجغرافية وزيادة الكثافة السكانية، ومنها الاقتصادية والتي يمكن حصرها في انعدام الموارد الاقتصادية، كل ذلك وغيره فرض على هذه الدولة الاستجابة لهذه التحديات ووضع خطط وانتهاج سياسات للخروج من هذه الوضعية المتردية. وبالفعل فقد كان لسنغافورة ما أرادت بفضل تفعيل هذه الخطط والسياسات وتجسيدها في الواقع بدء بانتقاء الموارد البشرية ذات الكفاءة لإدارة الشأن العام، ومرورا بإصلاح نظامي التعليم والتكوين، إلى الانفتاح وتحرير الأسواق مع حتمية إرفاق هذه السياسات بسياسات أخرى مكملة كالتزام الواقعية والصرامة في تنفيذ القرارات الصادرة عن القيادة العليا للبلد.
This study attempts to take stock of one of the most important international experiences in the fight against poverty. it is Singapore's experience. The state of Singapore lived in miserable conditions at all levels: political, social and economic. On the political front, independence is a source of concern because of the instability of the region and the fear of conflict in some neighboring countries, in terms of social welfare, poverty, deprivation and exploitation. were the most important manifestations of Singaporean society due to lack of natural resources and declining sources of income. As for the economic situation of the country, it also suffered from the effects and vestiges of the British and Japanese occupation, and the lack of clarity of the vision of the future. All this and others have forced the country to meet these challenges and to develop plans and policies to get out of this deteriorating situation. In fact, Singapore has gotten really excited about it by actually activating these plans and policies, starting with the selection of effective human resources and managing public affairs, through the reform of education and training systems, and the liberalization of markets, with the inevitability of linking These policies are in addition to those of the highest authorities in the application of the highest authorities. Through these sound plans and policies, Singapore has been able to advance economic growth, which has impacted all other areas of development.
Keywords: سنغافورة -- مكافحة الفقر -- التجربة السنغافورية